Understanding the life experiences of elderly in social isolation from the social systems perspective: using Hong Kong as an illustrating example - Lo, T. Wing; Chan, Gloria Hongyee (Frontiers in Psychiatry, 2023)
Aim: Elderly in social isolation, often referred to as older people who experience social alienation, with little social support from their family, peers, and community, suffer from a poor quality of life and well-being. Since their life experiences are affected by a range of factors from different levels, this study seeks to investigate their current life situations and experiences from a social systems perspective. Methods: A qualitative study was conducted to enrich the understanding of their current life situations and experiences and to generate corresponding practice implications. In this study, there were 13 elderly participants in social isolation, which were users of a social service agency in Hong Kong. They took part in a semi-structured individual interview, sharing their life stories about their daily lives, social relationships, and sense of well-being. Qualitative results were analyzed based on these dimensions. Results: Results showed that the elderly participants in social isolation had low level of social support and participation in social activities. Their life experiences and situations were affected by multiple levels of factors which were inter-related. Conclusion: Results support the application of social systems perspective in investigating the life conditions of elderly in social isolation. The corresponding practice implications were also discussed.